Optimization of The Boiling and Soaking Times of Tempeh With The Use Of Fuzzy Logic Method - Arief Wijaya; Atris Suryantohadi (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2005)
Boiling and soaking times of tempeh production processes are two factors influencing the quality of soybean fermentation of tempeh fungi (Rhizopus ologosporus sp.). An optimal production processes period would help reducing production costs and improve the quality of tempeh fungi. This study aimed at designing and applying fuzzy logic technique in optimizing boiling and soaking times to produce the top amount of tempeh product. Combination of boiling and soaking times of tempeh were used for composing fuzzy inference and fuzzy rule-based system. Soaking times were measured within interval 10 hours up to 40 hours. Boiling times were measured within interval 10 minutes to 60 minutes. The latter stage was used to compose fuzzy inference system. Using 24 fuzzy rules implemented in the system, the result was used to find the optimum boiling and soaking process timeduring tempeh production. Comparison with actual data was made by means of quadratic regression analysis (SEE=14) and found that fuzzy logic (SEE=2) was more accurate resulting in a lower error prediction value in finding the most optimum solution of the processes time.